Exploration of latent early literacy profiles in German kindergarten children using a newly developed app - Stuhr, Christina; Yumus, Melike; Meindl, Marlene; Jungmann, Tanja; Hughes, Charmayne Mary Lee (Frontiers in Education, 2024)
This study investigates the efficacy of the tablet-based EuLeApp© assessment tool in delineating distinct latent early literacy profiles among German kindergarten children aged between 4.0 to 7.0 years. Utilizing latent class analysis on a diverse sample of 285 children, we assessed various early literacy skills, including print awareness, concepts of print, word awareness, phonological awareness, alphabet knowledge, and narrative skills, using the app prototype. Furthermore, we examined how factors such as age, biological sex, and language impairment contribute to the manifestation and prevalence of these latent literacy profiles. Our analysis revealed four stable and interpretable early literacy profiles—Exceptional Performers (17%), Typical Performers (41%), Marginal Performers (35%), and Subpar Performers (7%) - shaped by the intricate interplay of age, biological sex, and language impairment status. These findings underscore the importance of employing person-centered methodologies to characterize early childhood literacy profiles, providing a framework for tailoring intervention programs to suit the unique characteristics and requirements of individual children.